AUDIT TEKNOLOGI INFORMASI DENGAN COBIT PADA SISTEM INFORMASI UNIVERSITAS METHODIST INDONESIA - Darwis Robinson Manalu (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Improving services in all fields in higher education is the main choice because it is closely related to stakeholder satisfaction, especially in the academic field. Information technology used in managing activities will determine the desired process and output. So it is necessary to evaluate and audit information technology to determine the achievement of performance or productivity. Universitas Methodist Indonesia has implemented Information Technology in managing academic activities ranging from new student registration to student graduation, lecturer and staff activities, research activities, and community service. COBIT is one of the tools used in auditing information systems and information technology. The audit is carried out on human resources related to system and technology management involving the Head of the Data Processing Center, Head of Administration and Information Services, Head of System Development Affairs, and Implementing Staff. To obtain data by making a questionnaire given to the audited party. From the test results on the effectiveness of the control, there is already a running control, namely PO8.1. Quality Management System, PO8.4. Customer Focus, PO8.5 Continuous Improvement, and PO8.6 Quality Measurement, Monitoring and Review, DS5.9. Malicious Software Prevention, Detection, and Correction need to be improved and continuously. Then the level of performance of the Detailed Control Objective (DCO) in the third party service management process still tends to be lacking and still needs to be improved, with the average performance value in the third party service management process being 1.5.